Relationships Among Maternal Traits and Sale Prices of Red Angus Bulls Sold at Auction From 2017 Through 2019 - M. J. Smith; K. E. Fike; M. E. King; E. D. McCabe; G. M. Rogers; K. G. Odde (Kansas Agricultural Experiment Station Research Reports, 2021)
Objective:The objective of this study was to evaluate the influence of maternal traits in the form of selection indices and expected progeny differences on the sale price of Red Angus Bulls sold at auction from 2017 through 2019 across the United States. Study Description:Information describing factors about Red Angus bulls marketed through auctions were obtained from the Red Angus Association of America (Commerce City, CO) in an electronic format. Data were collected for 21,362 Red Angus bulls offered for sale in auctions from 2017 through 2019. Multiple regression models were developed using backward selection procedures to examine the effect of maternally-related genetic factors in the form of selection indices and expected progeny differences on bull sale price. Results:Various maternal factors in the form of selection indices and expected progeny differences were significant factors influencing Red Angus bull sale price. Sale price was found to be positively associated with HerdBuilder Index. Results indicated significant relationships between sale price and various expected progeny differences including calving ease direct expected progeny difference, maintenance energy expected progeny difference, heifer pregnancy expected progeny difference, calving ease maternal expected progeny difference, and stayability expected progeny difference. However, relatively low R2values across both models indicate that only a small amount of the price variation was accounted for, suggesting that buyers are utilizing additional information when making purchasing decisions that we are not able to fully characterize. The Bottom Line:In addition to genetic factors, buyers may be considering other characteristics not captured within this data such as physical attributes, marketing tactics, and breeder reputation. Continued research and understanding of the various maternal factors affecting beef bull sale price may prove valuable to this sector of the beef industry.
Keywords: beef bulls; expected progeny differences; selection indices